1973
DOI: 10.1126/science.179.4069.133
|View full text |Cite
|
Sign up to set email alerts
|

Isospin in Nuclei

Abstract: The major feature of isospin in nuclei that I have discussed here is its application to all nuclei. The rebirth of this quantum number in nuclear physics occurred in the early 1960's and was initiated almost entirely by the important work of Anderson et al. (4) and Fox et al. (5). There is still great interest in the use of isospin in its fullest sense as predicted by Wigner (3), and indeed isospin concepts have been largely responsible for demonstrating that nuclei in the doubly "magic number" region of (208)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…According to Wigner, isospin, a fundamental entity in nuclear physics, can enable us to obtain the value of a physical quantity which is more difficult to measure, from a quantity which is easier to measure or which has already been measured [1]. In 1960s, important work of Andersson et al, [2] and Fox et al, [3] in the A = 50 and 90 mass regions, respectively, lead to the rebirth of this quantum number [4]. Lane and Soper [5] extended the work of MacDonald [6] for light nuclei and investigated the degree of isospin purity in heavier nuclei.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wigner, isospin, a fundamental entity in nuclear physics, can enable us to obtain the value of a physical quantity which is more difficult to measure, from a quantity which is easier to measure or which has already been measured [1]. In 1960s, important work of Andersson et al, [2] and Fox et al, [3] in the A = 50 and 90 mass regions, respectively, lead to the rebirth of this quantum number [4]. Lane and Soper [5] extended the work of MacDonald [6] for light nuclei and investigated the degree of isospin purity in heavier nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical work suggested that the isospin may become a good quantum number in heavy nuclei. The large number of excess neutrons in neutron-rich nuclei together have an absolutely pure isospin, which strongly dilutes the isospin impurity of the remaining part of the system with N=Z [4,5]. The fission fragments of heavy nuclei are highly neutron rich with the value of T 3 = (N-Z)/2 becoming very large [4] and are expected to carry a pure isospin.…”
Section: Introductionmentioning
confidence: 99%
“…17,....,29 from Eq. (7) and if it does not, then we exclude that particular combination. We obtain 6 possible combinations for Ru-Pd partition as listed in Table 3.…”
Section: Assignments Of Isospin Formentioning
confidence: 99%
“…Bohr and Mottelson [5] have also discussed this idea and concluded that even in heavy nuclei, the probability of the Coulomb interaction causing mixing of higher isospin states with the ground state is small. Robson again reiterated in 1973 [6] that 'Isospin has been reborn as an important and useful quantum number for all nuclei' including heavy nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…
It is generally believed that isospin would diminish in its importance as we go towards heavy mass region due to isospin mixing caused by the growing Coulomb forces. However, it was realized quite early that isospin could become an important and useful quantum number for all nuclei including heavy nuclei due to neutron richness of the systems [1]. Lane and Soper [2] also showed in a theoretical calculation that isospin indeed remains quite good in heavy mass neutron rich systems.
…”
mentioning
confidence: 99%